Autonomic Nervous System Response Patterns of Test-Anxious Individuals to Evaluative Stress - Bian, Wenjun; Zhang, Xiaocong; Dong, Yunying (Frontiers in Psychology, 2022)
Test anxiety is a widespread and primarily detrimental emotion in learning and achievement settings. This research was conducted to explore the autonomic nervous system (ANS) response patterns of test-anxious individuals in response to evaluative stress. By presenting a standard interview task, an evaluative scenario was effectively induced. Heart rate variability (HRV), a bio-marker which can accurately reflect the ANS activity, was used to reflect the physiological responses of 48 high test-anxious subjects and 49 low test-anxious subjects. The results indicated that: (1) both groups showed a significant increased emotional arousal in the evaluative scenario; (2) high test-anxious individuals showed a significant decreased emotional pleasantness in the evaluative scenario, whereas low test-anxious individuals showed no significant changes; (3) both groups showed an increased low-frequency HRV; (4) high test-anxious individuals showed a significant decreased high-frequency HRV and root mean square of successive heartbeat interval differences (RMSSD), whereas low test-anxious individuals remained stable. These findings suggest that high test-anxious individuals display an increased sympathetic nervous system (SNS) activity and decreased parasympathetic nervous system (PNS) activity in response to evaluative stress, while low-anxious individuals display an increased SNS activity and stable PNS activity in response to evaluative stress.